Conservation Easements: Options for Preserving Current Land Uses - Chris Demers; Douglas R. Carter (EDIS)
Conservation easements are cost-effective means for government agencies or non-government conservation organizations to protect land. Instead of purchasing land outright, these agreements allow organizations to purchase the development rights of a property. This protects the land and saves money. Landowners who choose this option prevent future residential and commercial development of their land, and reduce the amount of inheritance tax liability. Landowners are encouraged to enter such agreements carefully because they require several rights to be conveyed to the easement grantee and the duration of these agreements is typically perpetual. This revised 5-page fact sheet describes conservation easements, what is involved in establishing one, tax implications, participating government and non-government organizations, and important considerations for landowners. Written by Chris Demers and Douglas R. Carter, and published by the UF Department of School of Forest Resources and Conservation, March 2014.